Zanobi Acciaioli, Oratio in laudem Civitatis Neapolitanae, ed. Antonietta Iacono, Napoli, Paolo Loffredo, 2023 - Nicoletta Rozza (CESURA, 2023)
Lettura di Zanobi Acciaioli, Oratio in laudem Civitatis Neapolitanae, ed. Antonietta Iacono, Napoli, Paolo Loffredo, 2023